2020
DOI: 10.1108/ecam-06-2019-0283
|View full text |Cite
|
Sign up to set email alerts
|

A holistic review of research on carbon emissions of green building construction industry

Abstract: Purpose Addressing global warming challenge, carbon emissions reduction potential of the construction industry has received additional attentions. The decoupling of construction industry and carbon emissions through policies, technologies and model innovations is an effective way for reducing environmental pollution and achieve eco-urban target. The paper aims to discuss these issues. Design/methodology/approach Within the scope of green building carbon emissions (GB-CO2) research, a large number of scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 132 publications
(229 reference statements)
1
39
0
Order By: Relevance
“…rough proper planning of the transport vehicles, the problem can be described as passing through the loading and unloading points in a certain order on the premise of meeting a series of constraints (load, demand, transportation time, etc.) and achieve certain goals, such as the minimum or maximum distance, time, and cost [15,21]. In an actual transportation process, the distribution of several goods needs to have specific time requirements to complete the transportation service between the earliest and latest time specified by customers, thus forming a time window [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…rough proper planning of the transport vehicles, the problem can be described as passing through the loading and unloading points in a certain order on the premise of meeting a series of constraints (load, demand, transportation time, etc.) and achieve certain goals, such as the minimum or maximum distance, time, and cost [15,21]. In an actual transportation process, the distribution of several goods needs to have specific time requirements to complete the transportation service between the earliest and latest time specified by customers, thus forming a time window [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the annual report released by the European Environment Agency, 72% of the energy consumption of the global transportation sector comes from road vehicles [13,14]. erefore, ways to reduce transportation energy consumption in the process of component transportation are a significantly important role in the development of "green buildings" [15,16]. e prefabricated components for the prefabricated buildings must be produced in strict accordance with the production plan [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the construction industry the green innovation can be a potencial sector with ability to lead the process sustainables and thus be a pioneer in sustainable development [26]. For example, green roofs have been used by humanity since ancient times, because people lacked the usual building materials, such as stone and wood, and the means to make bricks and tiles; currently some buildings and homes use them but it should be more used due to the great benefits that it generates to both human beings in their lives and the reduction of greenhouse gases to the environment [24] the importance of creating ecological buildings in order to reduce carbon emissions and the energy they consume, green innovation is applied to the design and use of suitable materials to make this industry friendlier to the environment and provide better quality of life to human beings [5].…”
Section: B Green Innovation Applications In the Construction Industrymentioning
confidence: 99%
“…with the increase in the potential for the consumption of global natural resources, greenhouse gas emissions (GHG) have been produced that have generated a series of problems, such as environmental damage in oceans and rivers, perforation of the ozone layer, increased climate change and global warming [4]. The construction group consume more than 40% of total global energy and is demonstrated by more the 40% of global GHG emissions that are constantly emitted [5] and nowadays this number only falls to around 32% [6]. This has raised great public concern and people are increasingly alert to the importance of concept and application of green innovation in the construction industries and in other fields where it is applicable in relation to large industries [7].…”
Section: Introductionmentioning
confidence: 99%
“…Buildings have a significant impact on the natural environment, and they account for a significant proportion of global warming due to greenhouse gas (GHG) emissions (Alrashed and Asif, 2014;Ingrao et al, 2018). It has been reported that the built environment consumes 40% of worldwide energy and is responsible for one-third of the GHGs, which cause carbon emissions (Ching and Shapiro, 2014;Lu et al, 2020). In Saudi Arabia, buildings consume about 80% of total electrical energy at the national level during the operational phase.…”
Section: Introductionmentioning
confidence: 99%